Rural Development Planning in Africa (Palgrave Macmillan US, 2018)
This book applies a range of theories that focus on current concerns in rural Africa. The contributors lay out the conceptualization, analysis, methods, assumptions, perceptions, and ideas considered in each individual case. Specifically, this project inspires research in the field of rural development in Africa through multi-faceted endeavors that promote the ability of planning to uplift people's well-being and quality of life. .